Study of the Sediment Pollutant Evaluation and Resource Utilization in the North Canal - YAN Yulin (Renmin Zhujiang)
To understand the physical properties and pollution degree of the sediment in the North Canal,this paper collects the sediment in sections of North Canal with a columnar sampling device,and determines the physical properties,nutrient salt and heavy metal content of sediment.The results indicate that the average value of organic matter,TN and TP were 30.39 g/kg,0.161% and 0.174%,respectively,and were primary section, tertiary section and quaternary section according to the evaluation criterion.The average value of Cd,Cr,Ni,Zn,Cu,Pb and As were 0.39、86.55、29.09、199.82、52.27、33.86 and 8.26 mg/kg,respectively,which exceeded the background values for soil in Beijing.The evaluation results of geo-accumulation index show that the upper reach was partial moderate pollution,among which Cd and Zn were moderate pollution,and the middle and lower reaches were mild pollution.The average content of heavy metals was below the light pollution,so the pollution is not serious.Besides,the sediment can be reused to agricultural land and used as levee material,which exploit the way of resource utilization.